Exploration of factors influencing teachers’ responses to student misbehaviour in Maldivian secondary education - Ahmed, Nasrulla; Md Sidek, Suzana Suhailawaty (Islamic University of Maldives, 2025)
This study examines teachers› responses to classroom discipline and student misbehaviour in Maldivian secondary schools. The study was guided by two research questions that explored the disciplinary strategies teachers use and how these strategies influence student behaviour. A quantitative, cross-sectional survey design was employed, collecting data from 141 secondary school teachers through online questionnaires. These participants were selected using a stratified random sampling technique to ensure representation across different school settings. The findings indicate variability in teachers› intervention methods, with reinforcement emerging as the most used strategy. These results highlight the need for teacher training programs that emphasize effective classroom management techniques. Additionally, the study suggests policy-level interventions to support evidence-based discipline strategies in Maldivian schools. Further research with a larger sample size is recommended to gain deeper insights into the effectiveness of various disciplinary approaches.